Validating the Persian Version of Questionnaire of Educational and Learning Capital (QELC) in Iran - Niknam, Karim; Baloğlu, Mustafa (Chowanna, 2022)
Unlike the traditional person-centred models where character traits are attached to the actions, the Actiotope Model of Giftedness (AMG) focuses on the person-environment interactions. The model asserts that successful learning requires essential sources including learning and educational capital situated in the environment. This study aims to validate the Persian version of the Questionnaire of Educational and Learning Capital (QELC) among students in Iran (n = 283). The Persian QELC was prepared and utilised to evaluate the sources revealed in the AMG. Results show that the Persian QELC has satisfactory psychometric properties.